The Role of Lipid Metabolism in T Lymphocyte Differentiation and Survival - Howie, Duncan; Ten Bokum, Annemieke; Necula, Andra Stefania; Cobbold, Stephen Paul; Waldmann, Herman (Frontiers in Immunology, 2018)
AbstractThe differentiation and effector functions of both the innate and adaptive immune system are inextricably linked to cellular metabolism. The features of metabolism which affect both arms of the immune system include metabolic substrate availability, expression of enzymes, transport proteins and transcription factors which control catabolism of these substrates, and the ability to perform anabolic metabolism. The control of lipid metabolism is central to the appropriate differentiation and functions of T lymphocytes, and ultimately to the maintenance of immune tolerance.This review will focus on the role of fatty acid metabolism in T cell differentiation, effector function and survival. Fatty acids are important sources of cellular energy, stored as triglycerides. They are also used as precursors to produce complex lipids such as cholesterol and membrane phospholipids. Fatty acid residues also become incorporated into hormones and signalling moieties. Fatty acids signal via nuclear receptors and their channelling, between storage as triacyl glycerides or oxidation as fuel, may play a role in survival or death of the cell. In recent years progress in the field of immunometabolism has highlighted diverse roles for fatty acid metabolism in CD4 and CD8 T cell differentiation and function. This review will firstly describe the sensing and modulation of the environmental fatty acids and lipid intracellular signalling, and will then explore the key role of lipid metabolism in regulating the balance between potentially damaging pro-inflammatory and anti-inflammatory regulatory responses. Finally the complex role of extracellular fatty acids in determining cell survival will be discussed.